Outcomes of front‐line ibrutinib treated CLL patients excluded from landmark clinical trial. Issue 11 (26th September 2018) - Mato, Anthony R.; Roeker, Lindsey E.; Allan, John N.; Pagel, John M.; Brander, Danielle M.; Hill, Brian T.; Cheson, Bruce D.; Furman, Richard R.; Lamanna, Nicole; Tam, Constantine S.; Handunnetti, Sasanka; Jacobs, Ryan; et al.
Abstract: Ibrutinib demonstrated superior response rates and survival for treatment‐naïve chronic lymphocytic leukemia (CLL) patients in a pivotal study that excluded patients younger than 65 (<65) and/or with chromosome 17p13 deletion (del[17p13]). We examined outcomes and toxicities of CLL patients who would have been excluded from the pivotal study, specifically <65 and/or those with del[17p13]. This multicenter, retrospective cohort study examined CLL patients treated with front‐line ibrutinib at 20 community and academic centers, categorizing them based on key inclusion criteria for the RESONATE‐2 trial: <65 vs ≥65 and present vs absent del[17p13]. Of 391 included patients, 57% would have been excluded from the pivotal study. Forty‐one percent of our cohort was <65, and 30% had del(17p13). Patients <65 were more likely to start 420 mg of ibrutinib daily; those who started at reduced doses had inferior PFS. The most common adverse events were arthralgias, fatigue, rash, bruising, and diarrhea. Twenty‐four percent discontinued ibrutinib at 13.8 months median follow‐up; toxicity was the most common reason for discontinuation, though progression and/or transformation accounted for a larger proportion of discontinuations in <65 and those with del(17p13). Response rates were similar for <65 and those with del(17p13). However, patients with del(17p13) had inferior PFS and OS. Ibrutinib in the front‐line setting has extended beyond the population in which it was initially studied and approved. This study highlights and compares important differences in ibrutinib dosing, treatment interruptions, toxicities, reasons for discontinuation, and survival outcomes in two important patient populations not studied in RESONATE‐2.